Preparation method of metal nanoparticle-loaded nitrogen-doped carbon aerogel lithium ion battery negative electrode material
Patent Information
- Application Number
- CN202611083263.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-21
- Publication Date
- 2026-10-20
AI Technical Summary
[0006]本发明的目的是,为了解决传统碳基锂离子电池负极材料储锂容量低、过量氮掺杂导电性下降、缺少三维连续贯穿孔道等问题,提出一种负载金属纳米粒子的氮掺杂碳气凝胶锂离子电池负极材料的制备方法
[0013]本发明的有益效果是:本发明在增加碳基锂离子电池负极材料的储锂容量的同时,增加材料的导电性和离子传输速率,进而提高碳基锂离子电池负极材料的储锂容量和循环稳定性。首先,增加碳基锂离子电池负极材料的储锂容量,本发明以氮掺杂的形式在碳骨架中引入外源缺陷,构筑更多储锂活性位点,从而提高锂离子电池负极材料的储锂容量;然后,增加氮掺杂碳基锂离子电池负极材料的导电性,本发明在氮掺杂碳基质中引入金属纳米粒子,金属纳米粒子本身具有优良的导电性,从而解决氮掺杂碳基锂离子电池负极材料导电性差的问题;最后,增加离子传输传输速率,本发明构建三维多孔结构的碳气凝胶,三维连续贯通的多孔结构提供了巨大的接触面积,既可为储锂反应提供充足反应空间,又能大幅优化离子传输效率。
Smart Images

Figure FT_1 
Figure FT_2 
Figure FT_3
Abstract
Description
Technical Field
[0001] This invention relates to the field of lithium-ion battery energy storage materials technology, specifically to a method for preparing a nitrogen-doped carbon aerogel lithium-ion battery anode material loaded with metal nanoparticles. Background Technology
[0002] With fossil fuel reserves dwindling, developing clean and renewable energy sources has become a highly valuable research area for achieving sustainable development. Rechargeable lithium-ion batteries are promising energy storage devices, widely used in consumer electronics, portable devices, and many other fields. However, the theoretical specific capacity of commercially available graphite anodes is only 372 mAh•g. -1 There are obvious bottlenecks in this field, therefore, developing high-performance lithium-ion battery anode materials is crucial for further improving the electrochemical performance of lithium-ion batteries.
[0003] In recent decades, carbon-based materials have been extensively studied as potential anode materials for lithium-ion batteries due to their low cost, readily available raw materials, excellent conductivity, and outstanding physicochemical stability. Through rational structural design and controllable preparation of carbon-based materials, it is hoped that battery performance can be further improved to meet the ever-growing demands of future energy technologies. Carbon aerogels, belonging to three-dimensional porous carbon materials, have become ideal anode candidates for lithium-ion batteries due to their unique structural advantages such as large specific surface area, interconnected pore networks, and excellent conductivity. These structural advantages not only provide abundant active sites for lithium-ion intercalation and deintercalation processes but also accelerate electron and ion transport, thereby improving the electrochemical performance of the anode. However, pure carbon aerogels generally suffer from low reversible capacity and mediocre rate performance, limiting their practical applications.
[0004] Introducing heteroatom doping into carbon aerogels is an effective way to improve their electrochemical activity. Nitrogen atoms, with sizes similar to carbon atoms, are the most commonly used doping elements. Nitrogen doping can introduce exogenous defects into the carbon framework, constructing more lithium storage active sites. CN118026150B provides a nitrogen-doped carbon nanosheet for lithium-ion batteries and its preparation method. The obtained nitrogen-doped carbon nanosheets, as a negative electrode material for lithium-ion batteries, have advantages such as high initial coulombic efficiency, high discharge capacity, and good rate performance. However, excessive nitrogen doping can destroy the graphitized carbon framework, causing a decrease in the material's conductivity. Introducing metal nanoparticles into the carbon negative electrode system can further regulate its electrochemical performance. For example, although cobalt nanoparticles do not directly participate in the lithium-ion redox reaction during charge and discharge, they can act as highly efficient electrocatalytic sites to accelerate the electrochemical reaction and improve the material's specific capacity and cycle reversibility. When preparing nitrogen-doped carbon composite materials using ZIF-67 as a precursor for lithium-ion batteries, the excellent conductivity of metallic cobalt itself can significantly improve the conductivity of the nitrogen-doped carbon matrix. It is worth noting that the ZIF-67-derived polyhedral particles are isolated from each other, lack continuous channels, and have micropores as the main pore structure. Charge carriers need to cross the phase interface multiple times, making it difficult to further improve the electrochemical performance.
[0005] Therefore, constructing a continuous interconnected network with a multi-level porous structure is essential for improving charge transport efficiency. Summary of the Invention
[0006] The purpose of this invention is to address the problems of low lithium storage capacity, decreased conductivity due to excessive nitrogen doping, and lack of three-dimensional continuous through-pores in traditional carbon-based lithium-ion battery anode materials, and to propose a method for preparing nitrogen-doped carbon aerogel lithium-ion battery anode materials loaded with metal nanoparticles.
[0007] The technical solution achieved by this invention is as follows: a method for preparing nitrogen-doped carbon aerogel lithium-ion battery anode material loaded with metal nanoparticles, wherein a precursor aerogel is obtained by crosslinking sodium alginate with metal ions, coordinating with organic ligands, and freeze-drying technology, and then converted into nitrogen-doped carbon aerogel lithium-ion battery anode material loaded with metal nanoparticles by high-temperature pyrolysis.
[0008] A method for preparing a nitrogen-doped carbon aerogel lithium-ion battery anode material loaded with metal nanoparticles, comprising the following steps: S1. Using a peristaltic pump, sodium alginate (SA) solution is added dropwise to the metal salt solution in the form of tiny droplets, where metal ions (M...) are present. n+ Under cross-linking action, SA droplets are transformed into metal ion-alginic acid (M... n+ -SA) hydrogel microspheres. The obtained M n+ -SA hydrogel microspheres are immersed in a 2-methylimidazole methanol solution. The 2-methylimidazole molecules will react with the M molecules inside the hydrogel microspheres.n+ A coordination reaction occurs to generate a metal-organic framework (MOF) structure, resulting in MOF-SA hydrogel microspheres; S2. The MOF-SA hydrogel microspheres obtained in step S1 are converted into MOF-SA aerogel microspheres by freeze-drying. S3. The MOF-SA aerogel microspheres obtained in step S2 are subjected to high-temperature pyrolysis under a protective atmosphere. The process is carried out in a tube furnace by adjusting the heating rate, constant temperature, and constant temperature holding time to obtain nitrogen-doped carbon aerogel lithium-ion battery anode material loaded with metal nanoparticles.
[0009] The sodium alginate solution has a mass concentration of 1-5 wt%; the metal salt solution has a mass concentration of 5-50 wt%; and the 2-methylimidazolium methanol solution has a mass concentration of 1-15 wt%.
[0010] The metal salt is one, two, or a combination of several of the following: cobalt nitrate, cobalt chloride, cobalt acetate, cobalt sulfate, ferric nitrate, ferric sulfate, ferric chloride, ferrous acetate, nickel nitrate, nickel sulfate, nickel chloride, nickel acetate, zinc nitrate, zinc sulfate, zinc chloride, and zinc acetate. The aforementioned metal salts encompass hydrated metal salts containing different amounts of water of crystallization, and the number of water molecules of crystallization is not limited.
[0011] The freeze-drying method is as follows: MOF-SA hydrogel microspheres are immersed in tert-butanol and solvent replacement is performed at a constant temperature of 30°C; the tert-butanol solution is replaced every 6 hours, with a total replacement time of 24 hours. After solvent replacement is completed, the MOF-SA tert-butanol gel microspheres are collected, pre-frozen for 1 day, and then transferred to a freeze dryer for vacuum freeze-drying for 2 days to finally obtain MOF-SA aerogel microspheres.
[0012] The protective atmosphere is nitrogen or argon, and the heating rate is 5~15℃•min. -1 The constant temperature is 700~1000℃, and the constant temperature is maintained for 1~5 hours.
[0013] The beneficial effects of this invention are as follows: This invention increases the lithium storage capacity of carbon-based lithium-ion battery anode materials while simultaneously increasing the conductivity and ion transport rate of the materials, thereby improving the lithium storage capacity and cycle stability of the carbon-based lithium-ion battery anode materials. First, it increases the lithium storage capacity of the carbon-based lithium-ion battery anode materials by introducing exogenous defects into the carbon framework through nitrogen doping, constructing more lithium storage active sites, thus improving the lithium storage capacity of the lithium-ion battery anode materials. Second, it increases the conductivity of the nitrogen-doped carbon-based lithium-ion battery anode materials by introducing metal nanoparticles into the nitrogen-doped carbon matrix. Metal nanoparticles themselves have excellent conductivity, thus solving the problem of poor conductivity in nitrogen-doped carbon-based lithium-ion battery anode materials. Finally, it increases the ion transport rate by constructing a three-dimensional porous carbon aerogel. The three-dimensional continuous porous structure provides a huge contact area, which can provide sufficient reaction space for the lithium storage reaction and significantly optimize ion transport efficiency.
[0014] The precursor metal ion-alginic acid hydrogel microspheres involved in this invention are prepared using a peristaltic pump, which is beneficial for large-scale preparation through a continuous flow synthesis process and is suitable for continuous and rapid preparation of high-performance lithium-ion battery anode materials. Attached Figure Description
[0015] Figure 1 The following is a flowchart of a method for preparing a nitrogen-doped carbon aerogel lithium-ion battery anode material loaded with metal nanoparticles according to the present invention: Figure 2 Here are actual photos and dimensions of the product from Example 1; Figure 3 Here is a scanning electron microscope (SEM) image of Example 1; Figure 4 The image is a transmission electron microscope (TEM) image of Example 1; Figure 5 The images shown are from a high-angle annular dark-field scanning transmission electron microscope (HAADF-STEM) and an energy dispersive spectroscopy (EDS) elemental distribution map of Example 1. Figure 6 The X-ray diffraction (XRD) patterns are shown for Example 1 and the comparative example. Figure 7 The Raman spectra of Example 1 and the comparative example are shown below; Figure 8 The N2 adsorption-desorption curves for Example 1 and the comparative example are shown below. Figure 9 This is a pore size distribution diagram for Example 1; Figure 10 The electrode in Example 1 is at 0.1 A•g -1 Typical charge-discharge curves at current density; Figure 11For Comparative Example 1, the electrode was at 0.1 A•g -1 Typical charge-discharge curves at current density; Figure 12 For comparative example 2, the electrode is at 0.1 A•g -1 Typical charge-discharge curves at current density; Figure 13 For comparative example 3, the electrode was at 0.1 A•g -1 Typical charge-discharge curves at current density; Figure 14 The electrode in Example 1 is at 0.1 A•g -1 Cyclic stability performance at current density. Detailed Implementation
[0016] The present invention will be described in detail below through specific embodiments, which will help those skilled in the art to further understand the present invention.
[0017] The flowchart of a method for preparing a nitrogen-doped carbon aerogel lithium-ion battery anode material loaded with metal nanoparticles in this embodiment is shown below. Figure 1 As shown.
[0018] Example 1 This embodiment is a nitrogen-doped carbon aerogel (Co / N-CA) lithium-ion battery anode material loaded with cobalt nanoparticles.
[0019] S1: Weigh 0.8 g of sodium alginate (SA) and dissolve it in 39.2 mL of deionized water. Place the mixture in a 50°C water bath and stir magnetically for 0.5 h until the SA powder is completely dissolved, obtaining a viscous solution. Let the resulting SA solution stand at room temperature for 3 h to remove internal air bubbles. Then, use a peristaltic pump to add the SA solution dropwise to 40 mL of a 37.5% (w / w) cobalt nitrate solution at a constant rate. Cobalt ions (Co...) 2+ It undergoes a cross-linking reaction with the active groups of SA molecules, rapidly generating Co. 2+ -SA hydrogel microspheres. The resulting Co... 2+ -SA hydrogel microspheres were further immersed in cobalt nitrate solution for 48 hours to ensure the cross-linking reaction proceeded fully. The fully cross-linked Co was then collected. 2+ -SA hydrogel microspheres were thoroughly washed with deionized water to remove free Co. 2+ The finished product Co was obtained. 2+ -SA hydrogel microspheres. Co... 2+ SA hydrogel microspheres were immersed in a 2-methylimidazole methanol solution (0.5 g 2-methylimidazole dissolved in 50 mL methanol) for 12 h, allowing the 2-methylimidazole molecules to react with Co. 2+ With sufficient coordination, ZIF-67 crystals are generated in situ inside the hydrogel microspheres, ultimately yielding ZIF-67-SA hydrogel microspheres.
[0020] S2: The ZIF-67-SA hydrogel microspheres obtained in step S1 were immersed in 30 mL of tert-butanol and placed in a 30°C constant temperature oven for solvent replacement. The tert-butanol was replaced every 6 hours, for a total replacement time of 24 hours. After solvent replacement, the microspheres were collected and pre-frozen for 1 day, and then placed in a freeze dryer for vacuum freeze-drying for 2 days to obtain ZIF-67-SA aerogel microspheres.
[0021] S3: Transfer the ZIF-67-SA aerogel microspheres obtained in step S2 into a tube furnace and heat them at 10 °C·min under a nitrogen atmosphere. -1 The temperature was increased to 800℃ at a certain heating rate and held at that temperature for 2 hours to obtain nitrogen-doped carbon aerogel (Co / N-CA) lithium-ion battery anode material loaded with cobalt nanoparticles. Figure 2 As shown, Co / N-CA has a black microsphere morphology with an average particle size of about 0.7 mm.
[0022] like Figure 3 As shown, scanning electron microscopy (SEM) reveals numerous channels on the tens of nanometer scale within the Co / N-CA structure, a typical structural feature of carbon aerogels. Furthermore, a large number of cobalt nanoparticles with a diameter of several nanometers are uniformly distributed within the three-dimensional network framework of the carbon aerogel. Transmission electron microscopy (TEM) results show (e.g.) Figure 4 As shown, cobalt nanoparticles are embedded within a carbon matrix, with a lattice spacing of 0.21 nm, matching the (111) crystal plane of metallic cobalt. The elemental distribution of Co / N-CA was characterized using high-angle annular dark-field scanning transmission electron microscopy (HAADF-STEM) imaging combined with energy dispersive spectroscopy (EDS) elemental mapping. Figure 5 (As shown). Cobalt has a larger atomic mass and exhibits greater contrast in the HAADF-STEM image, with its distribution perfectly matching that of cobalt (Co). Carbon (C) and nitrogen (N) are uniformly distributed in the matrix, demonstrating successful nitrogen doping into the carbon aerogel framework, which also serves as a carrier for cobalt nanoparticles. In this embodiment, thanks to the unique precursor structure of ZIF-67-SA aerogel microspheres, the Co / N-CA obtained through high-temperature pyrolysis inherits the hierarchical porous structure of the aerogel while achieving uniform nitrogen doping and uniform distribution of cobalt nanoparticles. Co / N-CA, possessing the triple advantages of nitrogen doping, a hierarchical porous carbon framework, and uniformly dispersed cobalt nanoparticles, exposes more active sites, improves material conductivity, ensures sufficient electrolyte wetting, and significantly enhances its electrochemical performance as a lithium-ion battery anode material.
[0023] Comparative Example 1 Comparative Example 1 was used to investigate the effect of the three-dimensional porous structure of aerogel on the electrochemical performance of the lithium-ion battery anode material in Example 1. A pure ZIF-67 precursor without aerogel structure was prepared according to existing conventional techniques, and then further prepared by high-temperature pyrolysis to obtain a nitrogen-doped carbon material Co / NC loaded with cobalt nanoparticles without aerogel structure. The specific preparation steps are as follows: 0.58 g of cobalt nitrate hexahydrate was weighed and added to 50 mL of deionized water. The solution was stirred continuously until completely dissolved to prepare a homogeneous solution A. 10 g of 2-methylimidazole was weighed and dissolved in 100 mL of deionized water. The solution was stirred thoroughly to prepare a solution B. Solution A was quickly poured into solution B, and after thorough mixing, the resulting precipitate was allowed to stand for 3 hours. The precipitate was then collected by centrifugation. The collected precipitate was washed twice with methanol, and after washing, it was dried in a 50°C oven for 12 hours to obtain pure purple ZIF-67 powder. The ZIF-67 powder was then pyrolyzed and carbonized under the same conditions as in Example 1 to obtain a black powdery Co / NC material (aerogel-free three-dimensional structure).
[0024] Comparative Example 2 Comparative Example 2 was used to investigate the contribution and effect of nitrogen doping on the structure and electrochemical performance of Example 1. Co-CA, a carbon aerogel material loaded with cobalt nanoparticles but without nitrogen doping, was prepared.
[0025] The overall preparation process, raw material ratio, reaction conditions, and carbonization parameters of the Co-CA material described in Comparative Example 2 are completely consistent with the preparation process of Co / N-CA in Example 1 of this invention. The only difference is that the 2-methylimidazole soaking coordination step is omitted. Finally, a carbon aerogel lithium-ion battery anode material loaded with cobalt nanoparticles and not doped with nitrogen is obtained, which is denoted as Co-CA.
[0026] Comparative Example 3 Comparative Example 3 was used to investigate the contribution of cobalt nanoparticles to the structure and electrochemical performance of Example 1. By etching away the cobalt nanoparticles in Co-CA, a pure carbon aerogel material CA without cobalt nanoparticles and without nitrogen doping was prepared.
[0027] The specific preparation method is as follows: the Co-CA material obtained in Comparative Example 2 is immersed in hydrochloric acid solution, and the cobalt nanoparticles embedded inside the material are completely removed by acid etching, finally obtaining pure carbon aerogel CA with completely removed cobalt nanoparticles. The rest of the preparation process of Comparative Example 3 is consistent with Comparative Example 2 and Example 1 of the present invention, except that the activity contribution of cobalt nanoparticles is eliminated by acid washing.
[0028] Figure 6The X-ray diffraction (XRD) patterns of four materials—Co / N-CA (Example 1), Co / NC (Comparative Example 1), Co-CA (Comparative Example 2), and CA (Comparative Example 3)—are shown. All four samples exhibit broadened diffraction peaks around 25°, indicating that the materials are predominantly composed of amorphous carbon or microcrystalline graphitic carbon. Comparison reveals that the XRD patterns of Co / N-CA, Co / NC, and Co-CA show three distinct characteristic diffraction peaks at 44.2°, 51.5°, and 75.5°, which correspond perfectly to the (111), (200), and (220) crystal planes of the cobalt standard card PDF#15-0806. No characteristic diffraction peaks of cobalt were detected in the CA sample, proving that the cobalt nanoparticles were completely etched away. Co / N-CA, Co / NC, and Co-CA have the same phase composition, but differ in pore structure and doping state.
[0029] Raman spectra at approximately 1340 cm⁻¹ -1 With 1580 cm -1 Two characteristic main peaks appeared at the location ( Figure 7 The former is peak D, originating from disordered carbon. A 1g Vibrational modes; the latter is the G peak, corresponding to the regular graphite lattice. E 2g Vibration mode. Peak intensity ratio of D peak to G peak. I D / I G It is a commonly used index for evaluating the internal defect density and structural disorder of carbon-based materials. Calculations have been performed on four materials: Co / N-CA, Co / NC, Co-CA, and CA. I D / I G The values were 0.92, 0.90, 0.91, and 0.92, respectively. All four samples showed low values. I D / I G The ratio is due to the fact that the cobalt nanoparticles embedded in the material have a catalytic graphitization effect, which improves the graphitization degree of the carbon matrix.
[0030] The BET specific surface areas of the four materials, Co / N-CA, Co / NC, Co-CA, and CA, are 438.6, 345.9, 364.5, and 651 m², respectively. 2 ·g -1 The CA material possesses a higher BET specific surface area because acid etching removes the internal cobalt nanoparticles. Figure 8It is evident that the nitrogen adsorption-desorption isotherm of Co / NC is a typical Type I isotherm, indicating that the material is predominantly microporous. In contrast, Co / N-CA, Co-CA, and CA all exhibit Type IV isotherm characteristics, indicating that their pore structure is predominantly mesoporous; in the low relative pressure range, all three simultaneously exhibit partial Type I isotherm characteristics, proving the presence of a certain degree of microporous structure within the material. Furthermore, the pore size distribution curve of Co / N-CA (e.g., ...) Figure 9 As shown, it confirms that it possesses a hierarchical porous structure that combines micropores and mesopores. This hierarchical pore structure provides sufficient sites for lithium-ion insertion / extraction on the one hand, and accelerates the transport and migration rates of electrons and ions on the other hand, ultimately significantly improving the electrochemical performance of the anode material.
[0031] Figures 10-13 The electrodes of Example 1 and each comparative example were tested at 0.1 A·g. -1 The charge-discharge curves at current density show that all samples were assembled using the exact same coin cell assembly process and electrochemical testing conditions. Figure 10 As shown, Co / N-CA exhibits the highest specific capacity during the first discharge cycle, reaching nearly 2000 mAh·g. -1 Furthermore, a distinct plateau characteristic appears in the low to medium potential region, indicating that its first-cycle reaction, except for Li... + Besides insertion / extraction, the process also involves SEI film formation, electrolyte decomposition, and cobalt species transformation, resulting in a relatively large irreversible capacity in the first cycle. However, starting from the second cycle, the charge-discharge curves gradually converge, indicating that the electrode interface stabilizes rapidly after initial activation, and subsequent reactions exhibit good reversibility, with the reversible capacity remaining at 1000 mAh·g. -1 The reversible capacities of the Co / NC, Co-CA, and CA electrodes are significantly lower, ranging from approximately 200 mAh·g. -1 ( Figure 11 (as shown), 400mAh·g -1 ( Figure 12 (as shown) and 275mAh·g -1 ( Figure 13 (As shown in the image). After 100 charge-discharge cycles, the reversible capacity of Co / N-CA still remains at 950 mAh·g. -1 ( Figure 14 As shown in the figure, the coulombic efficiency remains at around 98%. Co / N-CA exhibits excellent reversible capacity and cycling stability, thanks to its simultaneous cobalt nanoparticle loading, nitrogen doping, and three-dimensional continuous aerogel porous structure.
[0032] Example 2 This embodiment is a nitrogen-doped carbon aerogel (Fe / N-CA) lithium-ion battery anode material loaded with iron nanoparticles.
[0033] S1: Weigh 0.8 g of sodium alginate (SA) and dissolve it in 39.2 mL of deionized water. Place the mixture in a 50°C water bath and stir magnetically for 0.5 h until the SA powder is completely dissolved, obtaining a viscous solution. Let the resulting SA solution stand at room temperature for 3 h to remove internal air bubbles. Then, use a peristaltic pump to add the SA solution dropwise to 40 mL of a 37.5% (w / w) ferric nitrate solution at a constant rate. Iron ions (Fe...) 3+ It undergoes a cross-linking reaction with the active groups of SA molecules, rapidly generating Fe. 3+ -SA hydrogel microspheres. The formed Fe... 3+ -SA hydrogel microspheres were further immersed in ferric nitrate solution for 48 hours to ensure the cross-linking reaction proceeded fully. The fully cross-linked Fe was then collected. 3+ -SA hydrogel microspheres were thoroughly washed with deionized water to remove free Fe. 3+ The finished product Fe was obtained. 3+ -SA hydrogel microspheres. Fe... 3+ SA hydrogel microspheres were immersed in a 2-methylimidazole methanol solution (0.5 g 2-methylimidazole dissolved in 50 mL methanol) for 12 h, allowing the 2-methylimidazole molecules to react with Fe. 3+ With sufficient coordination, Fe-MOF crystals are generated in situ inside the hydrogel microspheres, ultimately yielding Fe-MOF-SA hydrogel microspheres.
[0034] S2: The Fe-MOF-SA hydrogel microspheres obtained in step S1 were immersed in 30 mL of tert-butanol and placed in a 30 °C constant temperature oven for solvent replacement. The tert-butanol was replaced every 6 h, for a total replacement time of 24 h. After solvent replacement, the microspheres were collected and pre-frozen for 1 day, and then placed in a freeze dryer for vacuum freeze-drying for 2 days to obtain Fe-MOF-SA aerogel microspheres.
[0035] S3: Transfer the Fe-MOF-SA aerogel microspheres obtained in step S2 into a tube furnace and heat them at 10 °C·min under a nitrogen atmosphere. -1 The temperature was increased to 800℃ at a certain rate and held at that temperature for 2 hours to obtain nitrogen-doped carbon aerogel (Fe / N-CA) lithium-ion battery anode material loaded with iron nanoparticles.
[0036] Example 3 This embodiment is a nitrogen-doped carbon aerogel (Cu / N-CA) lithium-ion battery anode material loaded with copper nanoparticles.
[0037] S1: Weigh 0.8 g of sodium alginate (SA) and dissolve it in 39.2 mL of deionized water. Place the mixture in a 50°C water bath and stir magnetically for 0.5 h until the SA powder is completely dissolved, obtaining a viscous solution. Let the resulting SA solution stand at room temperature for 3 h to remove internal air bubbles. Then, use a peristaltic pump to add the SA solution dropwise to 40 mL of a 37.5% (w / w) copper nitrate solution at a constant rate. Copper ions (Cu) 2+ It undergoes a cross-linking reaction with the active groups of SA molecules, rapidly generating Cu. 2+ -SA hydrogel microspheres. The formed Cu 2+ -SA hydrogel microspheres were further immersed in copper nitrate solution for 48 hours to ensure the cross-linking reaction proceeded fully. The fully cross-linked Cu was then collected. 2+ -SA hydrogel microspheres were thoroughly washed with deionized water to remove free Cu. 2+ The finished product Cu was obtained. 2+ -SA hydrogel microspheres. Cu 2+ SA hydrogel microspheres were immersed in a 2-methylimidazole methanol solution (0.5 g 2-methylimidazole dissolved in 50 mL methanol) for 12 h, allowing the 2-methylimidazole molecules to react with Cu. 2+ With sufficient coordination, Cu-MOF crystals are generated in situ inside the hydrogel microspheres, ultimately yielding Cu-MOF-SA hydrogel microspheres.
[0038] S2: The Cu-MOF-SA hydrogel microspheres obtained in step S1 were immersed in 30 mL of tert-butanol and placed in a 30 ℃ constant temperature oven for solvent replacement. The tert-butanol was replaced every 6 h, for a total replacement time of 24 h. After solvent replacement was completed, the microspheres were collected and pre-frozen for 1 day, and then placed in a freeze dryer for vacuum freeze drying for 2 days to obtain Cu-MOF-SA aerogel microspheres.
[0039] S3: Transfer the Cu-MOF-SA aerogel microspheres obtained in step S2 into a tube furnace and heat them at 10 °C·min under a nitrogen atmosphere. -1 The temperature was increased to 800℃ at a certain heating rate and held at that temperature for 2 hours to obtain nitrogen-doped carbon aerogel (Cu / N-CA) lithium-ion battery anode material loaded with copper nanoparticles.
[0040] This embodiment constructs a precursor MOF-SA aerogel and prepares a carbon aerogel lithium-ion battery anode material by high-temperature pyrolysis. The aerogel material possesses a three-dimensional hierarchical porous framework, uniform nitrogen doping, and highly dispersed metal nanoparticles. Compared with existing simple MOF-derived carbon materials, nitrogen-free carbon aerogels, and nitrogen-free pure carbon aerogels without metal nanoparticles, the material of this invention can expose a large number of electrochemical active sites, while accelerating electrolyte penetration and rapid ion and electron transport, significantly improving the electrochemical performance of lithium-ion battery anode materials. The preparation process is simple and controllable, the raw materials are readily available, and it is easy to carry out continuous production, showing good prospects for industrial application.
Claims
1. A method for preparing a nitrogen-doped carbon aerogel lithium-ion battery anode material loaded with metal nanoparticles, characterized in that, The method describes obtaining a precursor aerogel through ion-crosslinking of sodium alginate, organic ligand coordination, and freeze-drying, followed by high-temperature pyrolysis to convert it into nitrogen-doped carbon aerogel loaded with metal nanoparticles. The steps of the method are as follows: (1) Sodium alginate solution was dripped into metal salt solution in the form of tiny droplets using a peristaltic pump. Under the cross-linking effect of metal ions, the sodium alginate droplets were transformed into metal ion-alginic acid hydrogel microspheres. The obtained metal ion-alginic acid hydrogel microspheres were immersed in 2-methylimidazolium methanol solution. The 2-methylimidazolium molecules would undergo coordination reaction with the metal ions inside the hydrogel microspheres to generate metal-organic framework (MOF) structure, thus obtaining MOF-alginic acid hydrogel microspheres. (2) The MOF-algin hydrogel microspheres obtained in step (1) are freeze-dried to convert the MOF-algin hydrogel microspheres into MOF-algin aerogel microspheres. (3) The MOF-alginate aerogel microspheres obtained in step (2) are subjected to high-temperature pyrolysis under a protective atmosphere. The process is carried out in a tube furnace by adjusting the heating rate, constant temperature and constant temperature holding time to obtain nitrogen-doped carbon aerogel lithium-ion battery anode material loaded with metal nanoparticles.
2. The method for preparing a nitrogen-doped carbon aerogel lithium-ion battery anode material loaded with metal nanoparticles according to claim 1, characterized in that, The sodium alginate solution has a mass concentration of 1-5 wt%; the metal salt solution has a mass concentration of 5-50 wt%; and the 2-methylimidazolium methanol solution has a mass concentration of 1-15 wt%.
3. The method for preparing a nitrogen-doped carbon aerogel lithium-ion battery anode material loaded with metal nanoparticles according to claim 1, characterized in that, The metal salt is one or a combination of two or more of the following: cobalt nitrate, cobalt chloride, cobalt acetate, cobalt sulfate, ferric nitrate, ferric sulfate, ferric chloride, ferrous acetate, nickel nitrate, nickel sulfate, nickel chloride, nickel acetate, zinc nitrate, zinc sulfate, zinc chloride, and zinc acetate; the aforementioned metal salts cover hydrated metal salts containing different amounts of water of crystallization, and the number of water molecules of crystallization is not limited.
4. The method for preparing a nitrogen-doped carbon aerogel lithium-ion battery anode material loaded with metal nanoparticles according to claim 1, wherein the freeze-drying treatment method is as follows: MOF-alginic acid hydrogel microspheres were immersed in tert-butanol and solvent replacement was performed at a constant temperature of 30°C. The tert-butanol solution was replaced every 6 hours, with a total replacement time of 24 hours. After solvent replacement, the MOF-alginic acid tert-butanol hydrogel microspheres were collected, pre-frozen for 1 day, and then transferred to a freeze dryer for vacuum freeze drying for 2 days to finally obtain MOF-alginic acid aerogel microspheres.
5. The method for preparing a nitrogen-doped carbon aerogel lithium-ion battery anode material loaded with metal nanoparticles according to claim 1, wherein the protective atmosphere is nitrogen or argon, and the heating rate is 5~15℃•min. -1 The constant temperature is 700~1000℃, and the constant temperature is maintained for 1~5 hours.
Citation Information
Patent Citations
A nitrogen-doped carbon nanosheet applied to a lithium-ion battery and a preparation method thereof
CN118026150B